Radicava (edaravone) for amyotrophic lateral sclerosis: US experience at 1 year after launch. Issue 7 (2nd October 2019) - Jackson, Carlayne; Heiman-Patterson, Terry; Kittrell, Pamela; Baranovsky, Tatyana; McAnanama, Glenn; Bower, Laura; Agnese, Wendy; Martin, Mike
Abstract: Background : Radicava ® (edaravone), approved for the treatment of amyotrophic lateral sclerosis (ALS) in 2017, may be administered intravenously at clinic sites, infusion centers or at home. Objective : To gain insights into the utilization of Radicava ® at 1 year post-launch. Methods : Radicava ® usage data were collected, and a survey was conducted among 75 physicians. Adverse events (AEs) were identified from a post-marketing safety database from 8 August 2017 through 3 August 2018 (cutoff date). Results : As of 6 August 2018, 3007 ALS patients were treated with Radicava ® . Survey results indicated that 43% of patients received infusions at home, 32% in a clinician's office, and 26% at a referred site. Infusions were administered mainly via implanted port. The most commonly reported AEs were drug ineffective, death (not specified), therapeutic response unexpected, asthenia, fatigue, gait disturbance, disease progression, muscular weakness, fall, and dyspnea. Conclusions : The first year of Radicava ® availability to ALS patients in the US provided many key learnings that will help shape strategies for improved patient care.